Perceived Organizational Support, Budaya Organisasi, Kepuasan Kerja dan Pengaruhnya terhadap Employee Engagement pada PT Angkasa Pura I Bandara Juanda Surabaya - Agus Purbo Widodo; Endri Hariyati (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
This study was conducted with the object of PT Angkasa Pura I Juanda Airport Surabaya, involving 79 respondents who are employees of PT Angkasa Pura I Juanda Airport Surabaya. The variables of this study include three independent variables consisting of Perceived Organizational Support, Organizational Culture and Job Satisfaction, as well as one dependent variable, namely Employee Engagement. The analysis carried out on the results of the study includes testing the research instrument, Normality Test, Multicollinearity Test, Heteroscedasticity Test, multiple linear regression analysis, and hypothesis testing. The results of the analysis show that Perceived Organizational Support has a positive and significant influence on Employee Engagement. Organizational culture has a positive and significant influence on Employee Engagement. Job Satisfaction has a positive and significant influence on Employee Engagement. The value of the variation in changes in Employee Engagement is influenced by Perceived Organizational Support, Organizational Culture and Job Satisfaction by 84.1% while the remaining 15.9% is influenced by other variables.